MEMBANGUN KARAKTER INKLUSIF SEJAK DINI (PENANAMAN SIKAP TOLERANSI TERHADAP PERBEDAAN BAGI SISWA SD) - Sigit Fibrianto, Alan; Dwitha Yuniar, Ananda; Wahyu Apriadi, Deny (Jurnal Praksis dan Dedikasi Sosial, 2022)
BUILDING INCLUSIVE CHARACTER EARLY (CULTURING ATTITUDE OFTOLERANCE TO DIFFERENCES FOR ELEMENTARY SCHOOL STUDENTS Inclusiveness has recently become an exciting topic of study to be discussed. Each local government seeks to design and implement inclusion policies. Discussions about inclusion always link people with disabilities. People with disabilities are discriminated against in their social environment, both in terms of their accessibility to public facilities as well as the negative labels attached to them. Therefore, this inclusive character is essential to be built in the next generation of the nation as early as possible. This research aims to instill an inclusive character early on for students at SD Laboratorium UM by using participatory methods or being directly involved in creating an inclusive learning process. The learning process is very significant in shaping the behavior patterns and character of children. Thus, inclusive education implemented in elementary schools (SD) can form an inclusive character for individuals from an early age. Several factors underlie inclusive education implemented at the elementary level, including: (1) at the individual development stage, SD is a very good level in the process of character building; (2) elementary school age is the most active stage in getting to know the social environment; (3) stage in understanding the role; (4) the experiences and insights they gain will be constructed through strong memories. These four factors underlie the formation of their personality into an inclusive character. Inklusifitas akhir-akhir ini menjadi topik kajian yang menarik untuk dibahas. Setiap pemerintah daerah berupaya merancang dan mengimplementasikan kebijakan inklusi. Pembahasan mengenai inklusi selalu mengaitkan penyandang difabel. Para difabel terdiskriminasi dari lingkungan sosialnya, baik aksesibilitasnya terhadap sarana publik, maupun label negatif yang melekat pada mereka. Maka dari itu, karakter inklusif ini sangat penting untuk dibangun pada generasi penerus bangsa sedini mungkin. Penelitian ini bertujuan untuk menanamkan karakter inklusif sejak dini bagi siswa di SD Laboratorium UM dengan menggunakan metode partisipatoris atau terlibat langsung dalam menciptakan proses pembelajaran yang inklusif. Proses pembelajaran sangat signifikan dalam membentuk pola perilaku dan karakter anak. Sehingga, pendidikan inklusif yang diimplementasikan pada Sekolah Dasar (SD) mampu membentuk karakter inklusif bagi individu sejak dini. Ada beberapa faktor yang mendasari pendidikan inklusi diimplementasikan di tingkat SD antara lain: (1) pada tahap perkembangan individu, SD merupakan jenjang yang sangat baik dalam proses pembentukkan karakter; (2) usia jenjang SD adalah tahapan paling aktif dalam mengenal lingkungan sosialnya; (3) tahap dalam memahami peran; (4) pengalaman dan wawasan yang mereka peroleh akan terkonstruk melalui ingatan yang kuat. Keempat faktor itulah yang mendasari pembentukkan kepribadian mereka menjadi karakter yang inklusif.